Nuclear Structure Investigations in Yb isotopes - Zyriliou, Aikaterini; Mertzimekis, Theo J.; Chalil, Achment; Vasileiou, Polytimos; Pelonis, Stefanos; Efstathiou, Margarita; Stan, Lucian; Turturica, Andrei; Costache, Cristian; Mihai, Radu; Borcea, Ruxandra; Ujeniuc, Sorin; et al. (HNPS Advances in Nuclear Physics, 2022)
The medium-to-heavy mass ytterbium isotopes (70Yb) in the rare-earth mass region are known to be well-deformed nuclei, which can be populated to very high spin, and are predicted to exhibit interesting phenomena, such as shape coexistence. The lack of any experimental information on the structure of the neutron-rich 180Yb isotope and the lifetime of the 21+ state of 178Yb have greatly motivated this study, which can offer useful information for the collective behavior of neutrons and protons in neutron-rich Yb isotopes. A measurement was performed to investigate the population of excited states and a first measurement of the unknown 21+ lifetime of 178Yb by means of a two neutron-transfer reaction 176Yb(18O,16O)178Yb at energies 68-74 MeV using the ROSPHERE array at IFIN-HH, Romania.